2017
DOI: 10.18632/oncotarget.18224
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TUG1 promotes cervical cancer progression by regulating the miR-138-5p-SIRT1 axis

Abstract: Increasing evidences showed that long non-coding RNAs (lncRNAs) play vital roles in tumor progression. Recent studies indicated that lncRNA TUG1 was upregulated and promoted tumor processes in several cancers. However, the expression and underlying mechanism of TUG1 in cervical cancer remain unclear. In the present study, we found that TUG1 expression was upregulated in cervical cancer tissues and correlated with advanced clinical features and poor overall survival. TUG1 knockdown suppressed cervical cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 26 publications
2
78
0
Order By: Relevance
“…An increasing amount of research has revealed that lncRNAs can act as ceRNAs to competitively bind to the miRNAs response elements (MRE) to regulated miRNAs functions [27]. Li et al reported that TUG1 could act as ceRNAs to regulate SIRT1 expression by sponging miR-138-5p in cervical cancer [28]. In the current study we found that MALAT1 is a target of miR-30a-5p by computational analysis, luciferase reporter assays, and RT-PCR.…”
Section: Discussionsupporting
confidence: 57%
“…An increasing amount of research has revealed that lncRNAs can act as ceRNAs to competitively bind to the miRNAs response elements (MRE) to regulated miRNAs functions [27]. Li et al reported that TUG1 could act as ceRNAs to regulate SIRT1 expression by sponging miR-138-5p in cervical cancer [28]. In the current study we found that MALAT1 is a target of miR-30a-5p by computational analysis, luciferase reporter assays, and RT-PCR.…”
Section: Discussionsupporting
confidence: 57%
“…can act as a ceRNA to elevate epigallocatechin gallate (EGCG)triggered CTR1 expression through sponging hsa-mir-98-5p (Jiang, Wu, Wang, Huang, & Feng, 2016 (Zhu, Shi, Liu, Wang, & Li, 2017). HOTAIR can activate cervical cancer progression by inhibiting miR-326 (X.…”
Section: Discussionmentioning
confidence: 99%
“…Latterly, taurine upregulated gene 1 (TUG1) expression was proved to be enormously elevated in most cancers, for instance prostate cancer [11], breast cancer [12], endometrial cancer [13] and cervical cancer [14]. More than that, TUG1 was aberrantly aggrandized in HCC tissues, and it could promote cell growth and tumor formation by targeting KLF2 [15].…”
Section: Introductionmentioning
confidence: 99%